DEEP LEARNING FOR GESTURE ANALYSIS IN PERFORMANCE TRAINING - Sreeram, Anusha; Sharma, Pratibha; Mankad, Kairavi; Rawat, Kalpana; Sharma, Rahul Kumar; Patil, Milind (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Gesture analysis is an important element in performance training in various areas including dance, sports, theatre, music and rehabilitation, whereby accurate movement of the body, time and expressiveness is important to the overall quality. The method of traditional gesture evaluation is biased on professional observation, and this method is subjective, cumbersome and cannot be scaled. This paper describes a deep learning-based gesture recognition system in the area of performing training to provide objective and data-driven feedback and individualized skills acquisition. The suggested method combines pose estimation with the help of computer vision and the deep neural framework, such as Convolutional Neural Networks (CNNs) to extract spatial features and Long Short-Term Memory (LSTM) or Transformer models to model temporal motion. Multi-dimensional gesture characteristics like joint paths, velocity signals, symmetry, balance and rhythmical consistency are trained directly by video sequences without any physical feature engineering. The framework facilitates real time and offline analysis that enables performers to get corrective feedback in real time or performance longitudinally. Empirical analyses show that deep learning models are far more efficient than the traditional machine learning methods on accuracy of gesture identification, detection of temporal alignment, movement quality evaluation. It is also possible to score expressiveness, coordination and consistency quantitatively with the help of the system, which helps to train and measure progress. The proposed deep learning-based gesture analysis framework should have significant potential in intelligent performance training systems, online coach environments, and simulated learning environments, owing to the subjectivity reduction and increased accessibility.